Towards More Shared Decision Making in Dermatology: Development of Evidence-based Decision Cards for Psoriasis and Atopic Eczema Treatments - Francisca M. Vermeulen; Gayle E. van der Kraaij; Ronald A. Tupker; Anne Bijlsma; Hans Blaauwbroek; Francine Das; Tessa Geltink; Josine S. van der Kraan; Renske Kranenburg; Dirk J. van der Veen; Kristie Venhorst; Phyllis I. Spuls (Medical Journals Sweden, 2020)
In shared decision making (SDM) patients and physicians make treatment decisions together based on the best available evidence and the values and preferences of patients. SDM is very suitable for use in dermatological practice, but is infrequently applied by dermatologists. To support the application of SDM in dermatology we developed Decision Cards: 1-page overviews of possible treatment options, for use during a patient-physician consultation. Decision Cards provide answers to patients' most frequently asked questions, based on (inter)national guidelines, Summary of Product Characteristics, relevant literature, and clinical expertise. Three evidence-based Decision Cards were developed: 1 for biologicals or apremilast in psoriasis, and 2 for atopic eczema (1 for topical, photo- or systemic therapy, and 1 for systemic therapy only). More cards for psoriasis are currently in development. Patients, dermatologists and researchers collaborated in the development of the Decision Cards. This paper shares the framework used for the development of the Decision Cards, in order to support others in the development process.